The influence of biomechanical stability on bone healing and fracture-related infection: the legacy of Stephan Perren. Issue 1 (January 2021) - Foster, Andrew L.; Moriarty, T. Fintan; Zalavras, Charalampos; Morgenstern, Mario; Jaiprakash, Anjali; Crawford, Ross; Burch, Marc-Antoine; Boot, Willemijn; Tetsworth, Kevin; Miclau, Theodore; Ochsner, Peter; Schuetz, Michael A.; et al.
Highlights: Biomechanical stability plays a critical role in fracture healing. Although stability is often described to be essential for both prevention and treatment of FRI, the underlying mechanisms and the optimal degree of stability remain unknown. Clinical studies on the topic are challenging and therefore the scientific evidence on this topic is limited to experimental studies in laboratory animals. Future research is required, as improvements in the surgical management of FRI may be achieved by a better understanding of the role of stability. Abstract: Bone healing is a complicated process of tissue regeneration that is influenced by multiple biological and biomechanical processes. In a minority of cases, these physiological processes are complicated by issues such as nonunion and/or fracture-related infection (FRI). Based on a select few in vivo experimental animal studies, construct stability is considered an important factor influencing both prevention and treatment of FRI. Stephan Perren played a pivotal role in the evolution of our current understanding of the critical relationship between biomechanics, fracture healing and infection. Furthermore, his concept of strain theory and the process of fracture healing is familiar to several generations of surgeons and has influenced implant development and design for the past 50 years. In this review we describe the role of biomechanical stability on fracture healing, and provide a detailed analysis of the preclinical studies addressing this in the context of FRI. Furthermore, we demonstrate how Perren's concepts of stability are still applied to current surgical techniques to aid in the prevention and treatment of FRI. Finally, we highlight the key knowledge gaps in the underlying basic research literature that need to be addressed as we continue to optimize patient care.